ONCOLYTIC VIRUS FOR TREATING COLORECTAL CANCER BY USING COLORECTAL CANCER CELL-SPECIFIC INFECTIOUS NEWCASTLE DISEASE VIRUS AND COMPOSITION FOR TREATING COLORECTAL CANCER BY USING SAME - JEON, Ju Hee; JUNG, Bo Kyoung; AN, Yong Hee; JANG, Hyun; JANG, Jin Ju (2023)
The present invention relates to a colorectal cancer cell-specific M2-LVP-K1 virus comprising a mutant sialic acid binding domain, and a composition for treating a colorectal cancer comprising same. The mutant sialic acid binding domain of the present invention is prepared by using a directed evolution technique, and is substituted with a normal sialic acid binding domain in an HN protein which is a cell binding receptor, so as to prepare a recombinant Newcastle disease virus of which HCT116 cell-specific infectivity is improved. The M2-LVP-K1 recombinant Newcastle disease virus having improved colorectal cancer cell-specific infectivity is confirmed to have an improved effect on the HCT116 cell death compared to the existing normal recombinant Newcastle disease virus, and to have an excellent inhibitory effect on the growth of cancer tissues through in vivo experiments. The mutant recombinant Newcastle disease virus suggested by the present study relates to a therapeutic virus formulation that can induce reduced clinical symptoms, partial remission, or complete remission, through colorectal cancer cell death or colorectal cancer tissue reduction. La présente invention concerne un virus M2-LVP-K1 spécifique des cellules du cancer colorectal comprenant un domaine de liaison de l'acide sialique mutant, et une composition pour traiter un cancer colorectal le comprenant. Le domaine mutant de liaison à l'acide sialique de la présente invention est préparé en utilisant une technique d'évolution dirigée, et est substitué à un domaine normal de liaison à l'acide sialique dans une protéine HN qui est un récepteur de liaison cellulaire, afin de préparer un virus recombiné de la maladie de Newcastle dont l'infectivité spécifique des cellules HCT116 est améliorée. Il a été confirmé que le virus recombiné de la maladie de Newcastle M2-LVP-K1 possédant une infectivité améliorée et spécifique aux cellules du cancer colorectal possède un effet amélioré sur la mort des cellules HCT116 par comparaison avec le virus recombiné normal existant de la maladie de Newcastle, et possède un excellent effet inhibiteur sur la croissance des tissus cancéreux grâce à des expériences in vivo. Le virus mutant recombiné de la maladie de Newcastle proposé par la présente invention concerne une formulation virale thérapeutique pouvant induire une réduction des symptômes cliniques, une rémission partielle ou une rémission complète, par la mort des cellules du cancer colorectal ou la réduction des tissus du cancer colorectal. 본 발명은 대장암 세포 특이적 mutant sialic acid binding domain을 포함하는 M2-LVP-K1 바이러스 및 이를 포함한 대장암 치료용 조성물에 관한 것으로 본 발명의 mutant sialic acid binding domain은 directed evolution 기술을 이용하여 제작된 것으로 세포 결합 receptor 인 HN 단백질에 정상적인 sialic acid binding domain과 치환되어 제작된 재조합 뉴캐슬병 바이러스로서 HCT116 세포에 대한 특이적 감염성이 향상되게 하였다. 대장암 세포 특이적 감염성이 향상된 M2-LVP-K1 재조합 뉴캐슬병 바이러스는 HCT116 세포 사멸 효과가 기존의 정상적인 재조합 뉴캐슬병 바이러스에 비해 향상되었으며 in vivo 실험을 통해서 암조직 성장 억제 효과가 우수함을 확인하였다. 본 연구에서 제시된 Mutant 재조합 뉴캐슬병 바이러스는 대장암 세포 사멸 또는 대장암 조직 축소를 통해 임상 증상 감소, 부분 관해 또는 완전 관해를 유도할 수 있는 치료용 바이러스 제제에 관한 것이다.